Layanan Sosial pada Lansia Berbasis Keluarga di Griya Bahagia PMI Surakarta - Ulfasari, Jihan Hasna’ (Yayasan Alpatih Harapan Semesta, 2024)
The form of implementation of family-based social services at Griya Bahagia can be seen from the implementation of the family function in the social services themselves. This research aims was to examine the process of forming family-based social services in Griya Bahagia PMI Surakarta. The results of this study indicated that the purpose of the establishment of Griya Bahagia PMI was to humanize the elderly who were displaced like a family by accommodating, caring, and restoring their social functioning so that their lives will be more prosperous. Therefore, to support the process of forming family-based social services, the Griya Bahagia formed several activities that can implement the function of the family in accordance with the objectives of social services. The formation of Griya Bahagia with a family-based social service system was inseparable from the social construction process that included the mechanism of dialectical externalization, objectivation and internalization.